Sofia Valdez and the Vanishing Vote - Beaty, Andrea; Roberts, David 1970- (New York : Amulet Books, 2020)
Sofia is put in charge of overseeing a fair election for a class pet, but first the Questioneers must learn about elections and good journalism--and remember that being a community matters most. Includes facts about the Delano Grape Strike, presidential elections, journalism, and the importance of voting.
Keywords: Questions and answers -- Juvenile fiction; Pets -- Juvenile fiction; Schools -- Juvenile fiction; Politics, Practical -- Juvenile fiction; Journalism -- Juvenile fiction; Questions and answers -- Fiction; Pets -- Fiction; Schools -- Fiction; Politics, Practical -- Fiction; Journalism -- Fiction